FaÊ¿Äliyyah IstikhdÄm LuÊ¿bah al-KalimÄt al-MukaÊ¿abah fÄ« MahÄrah al-KitÄbah - Yati, Mardi; Febrianta, Rita (HuRuf Journal : International Journal of Arabic Applied Linguistic, 2023)
The research objectives were to find out the effectiveness of the use of word cube games in writing skills students at MTsN 4 Pasaman. The method used in this research is an experimental method with a quantitative approach. The total populations were 139 students and the samples were 68 students using a random sampling technique. The data analysis technique used spss20. Based on the post-test in the experimental class and control class to improve writing skills in grade 7 students researchers found outÂ that the experimental class used the word cube game with an average score of 84.86 and the control class did not use the word cube game had an average score of 75.93. Then t count 2.0302 is greater than 5% of t-table which is 1.997. Then the 2-tailed sig is 024 less than 0.05. From the following results, a comparison of educational outcomes in the two classes was found. The results of students in the experimental class that uses the cube word game are greater than the control class. Ø§Ù„Ù‡Ø¯Ù Ù…Ù† Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ù‡Ùˆ Ù„Ù…Ø¹Ø±ÙØ© ÙØ¹Ù‘Ø§Ù„ÙŠØ© Ø§Ø³ØªØ®Ø¯Ø§Ù… "Ù„Ø¹Ø¨Ø© Ø§Ù„ÙƒÙ„Ù…Ø§Øª Ù…ÙƒØ¹Ù‘Ø¨Ø©" ÙÙŠ Ù…Ù‡Ø§Ø±Ø© Ø§Ù„ÙƒØªØ§Ø¨Ø© Â Ù„Ø¯Ù‰ Ø·Ù„Ø§Ø¨ Ø§Ù„ÙØµÙ„ 7 ÙÙŠ Ø§Ù„Ù…Ø¯Ø±Ø³Ø© Ø§Ù„Ù…ØªÙˆØ³Ù‘Ø·Ø© Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠÙ‘Ø© Ø§Ù„ØÙƒÙˆÙ…ÙŠÙ‘Ø© 4 Ø¨Ø§Ø³Ø§Ù…Ø§Ù†. Ø§Ù„Ù…Ù†Ù‡Ø¬ Ø§Ù„Ù‘Ø°ÙŠ ØªØ³ØªØ®Ø¯Ù… Ø§Ù„Ø¨Ø§ØØ«Ø© ÙÙŠ Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« ÙŠØ¹Ù†ÙŠ Ø§Ù„Ù…Ù†Ù‡Ø¬ Ø§Ù„ØªÙ‘Ø¬Ø±ÙŠØ¨ÙŠÙ‘ Ø§Ù„Ù†Ù‘Ù‚ÙŠÙ‘ Ø¨Ù…Ø¯Ø®Ù„ Ø§Ù„Ø¨ØØ« Ø§Ù„ÙƒÙ…Ù‘ÙŠÙ‘. Ù…Ø¬ØªÙ…Ø¹ Ø§Ù„Ø¨ØØ« 139 Ø·Ø§Ù„Ø¨Ù‹Ø§ ÙˆØ¹ÙŠÙ†ØªÙ‡ Ù…ÙƒÙˆÙ†Ø© Ù…Ù† 68 Ø·Ø§Ù„Ø¨Ø§. ÙˆØ§Ø³ØªØ®Ø¯Ù…Øª ØªÙ‚Ù†ÙŠØ© ØªØÙ„ÙŠÙ„ Ø§Ù„Ø¨ÙŠØ§Ù†Ø§Øª spss20. Ø¨Ù†Ø§Ø¡ Ø¹Ù„Ù‰ Ø§Ù„Ø§Ø®ØªØ¨Ø§Ø± Ø§Ù„Ø¨Ø¹Ø¯ÙŠ ÙÙŠ Ø§Ù„ÙØµÙ„ Ø§Ù„ØªÙ‘Ø¬Ø±ÙŠØ¨ÙŠÙ‘ ÙˆØ§Ù„ÙØµÙ„ Ø§Ù„Ø¶Ù‘Ø§Ø¨Ø· Ù„ØªØ±Ù‚ÙŠÙ‘Ø© Ù…Ù‡Ø§Ø±Ø© Ø§Ù„ÙƒØªØ§Ø¨Ø© Ù„Ø·Ù„Ø§Ù‘Ø¨ Ø§Ù„ÙØµÙ„ 7. Ø¹Ø±ÙØª Ø§Ù„Ø¨Ø§ØØ«Ø© ÙÙŠ Ø§Ù„ÙØµÙ„ Ø§Ù„ØªÙ‘Ø¬Ø±ÙŠØ¨ÙŠÙ‘ Ø§Ù„Ù‘Ø°ÙŠ ÙŠØ³ØªØ®Ø¯Ù… Ù„Ø¹Ø¨Ø© Ø§Ù„ÙƒÙ„Ù…Ø§Øª Ø§Ù„Ù…ÙƒØ¹Ù‘Ø¨Ø© Ø¨Ù…ØªÙˆØ§Ø³Ø· Ù†ØªÙŠØ¬Ø© 84,86 ÙˆÙÙŠ Ø§Ù„ÙØµÙ„ Ø§Ù„Ø¶Ù‘Ø§Ø¨Ø· Ø§Ù„Ù‘Ø°ÙŠ Ù„Ø§ ÙŠØ³ØªØ®Ø¯Ù… Ù„Ø¹Ø¨Ø© Ø§Ù„ÙƒÙ„Ù…Ø§Øª Ø§Ù„Ù…ÙƒØ¹Ù‘Ø¨Ø© Ø¨Ù…ØªÙˆØ§Ø³Ø· Ù†ØªÙŠØ¬Ø© 75, 93. Ø«Ù…Ù‘ ØªØ§Ø¡ Ø§Ù„ØØ³Ø§Ø¨ Ù‡Ùˆ 2.302 Ø£ÙƒØ¨Ø± Ù…Ù† ØªØ§Ø¡ Ø§Ù„Ø¬Ø¯ÙˆÙ„ 5% Ù‡Ùˆ1.997. ÙˆØ«Ù…Ù‘ sig- 2 tailed Ù‡Ùˆ 024 Ø£ØµØºØ± Ù…Ù† 0,05. Ù…Ù† Ø§Ù„Ù†Ù‘ØªÙŠØ¬Ø© Ø§Ù„ØªÙ‘Ø§Ù„ÙŠØ© ÙˆØ¬Ø¯Øª Ø§Ù„Ù…Ù‚Ø§Ø±Ù†Ø© Ø¹Ù„Ù‰ Ù†ØªÙŠØ¬Ø© Ø§Ù„ØªÙ‘Ø¹Ù„ÙŠÙ… ÙÙŠ Ø§Ù„ÙØµÙ„ÙŠÙ†. Ù†ØªØ§Ø¦Ø¬ Ø§Ù„Ø·Ù‘Ù„Ø§Ù‘Ø¨ ÙÙŠ Ø§Ù„ÙØµÙ„ Ø§Ù„ØªÙ‘Ø¬Ø±ÙŠØ¨ÙŠÙ‘ Ø§Ù„Ù‘Ø°ÙŠ ØªØ³ØªØ®Ø¯Ù… Ù„Ø¹Ø¨Ø© Ø§Ù„ÙƒÙ„Ù…Ø§Øª Ø§Ù„Ù…ÙƒØ¹Ù‘Ø¨Ø© ÙÙŠÙ‡ Ø£ÙƒØ¨Ø± Ù…Ù† Ø§Ù„ÙØµÙ„ Ø§Ù„Ø¶Ù‘Ø§Ø¨Ø·.